The Role of Target Therapy in the Treatment of Gastrointestinal Noncolorectal Cancers: Clinical Impact and Cost Consideration - Berretta, Massimiliano; Romano, Carmela; Di Francia, Raffaele; De Diviitis, Chiara; Canzonieri, Vincenzo; Caraglia, Michele; Facchini, Gaetano; Nasti, Guglielmo (Current Cancer Drug Targets, 2018)
Gastrointestinal (GI) tumors are among the leading cause of death in cancer patients worldwide. Particularly, gastric cancer (GC) is the third cause of cancer deaths, whereas esophageal neoplasm is the eighth leading most common cancer worldwide and its incidence, especially adenocarcinoma type, is continuously increasing. Also, Hepatocellular carcinoma, Cholangiocarcinoma and pancreatic cancer represent a very interesting model to multidisciplinary approach and recently new drugs are used in their treatment. Currently, new clinical trials are designed including classic chemotherapy in association with either small molecule inhibitors (i.e. Tyrosine Kinase inhibitors) and/or monoclonal antibody (i.e. anti-EGFR antibody). Moreover, a comprehensive list of new molecules for target therapy is included in this issue. The development of new treatment modalities (multidisciplinary approach) and targeted therapy approaches have contributed to improving the outcome in these cancer diseases. During the past few years, remarkable progress in molecular biology of malignancy, the discovery of specific targets, and the resulting development of systemic drugs that block critical kinases and several molecular pathways have all contributed to progress in cancer treatment, also in GI non-colorectal cancer treatment.
Keywords: clinical aspects